Changing Motifs in Arthurian Literature: Towards a New Round Table (Philologia, 2021)
The latest Arthurian Literature is changing the ideas we had about its characters, motifs and main important adventures and chapters.Old topics and characters, long-forgotten since the medieval tradition, are back in the Arthurian universe. More important, there is a new view on religion, contemptuous at times, a different reshaping of characters, and a new perspective of what we could consider Arthurian minorities.This article analyses some of these changes as represented in some of the most representative texts in modern Arthuriana and studies them from a historical, cultural and comparative perspective.
Keywords: Early Arthurian literature; modern Arthurian literature; religion; propaganda; Bernard Cornwell